Nanomaterials in diagnosis and treatment of cardiovascular diseases. (4th February 2023) - Zhao, Xiaoqi; Wang, Chunguang; Sun, Zhiguang; Yao, Nan; Zhang, Aiting; Guo, Shengyu
This paper prepared a nucleic acid aptamer functionalised magnetic ball/gold nanorod composite material. This multifunctional composite material can realise the reversible regulation of thrombin activity and assist in the diagnosis and treatment of cardiovascular diseases. Thrombin and its pair of nucleic acid aptamers can be built into a closed-loop structure based on the hybridisation technology of adjacent surfaces. The measurement of human serum coagulation time proves that this inhibition and recovery method has very good clinical application prospects. In the application of multi-functional nanomaterials to assist sports rehabilitation training, the paper analyses the level of serum N-terminal brain natriuretic peptide precursor (NT-pro BNP), high-sensitivity myocardial troponin T (hscTnT) and heart function indexes in patients with chronic heart failure influences. The results show that the use of multifunctional nanomaterials combined with exercise rehabilitation therapy in patients with chronic heart failure can significantly reduce serum NT-pro BNP and hscTnT levels and improve cardiovascular function.